Pharmacological regulation of striatal gene expression by metabotropic glutamate receptors - Wang John Qiang; Mao Li-ming (Acta Pharmacologica Sinica, 2016)
Metabotropic glutamate receptors (mGluR) are densely expressed by striatal medium spiny neurons. Activation of mGluR in this brain region alters local transmitter release and behaviors of experimental animals. In particular, mGluR regulate transcription factor and neuropeptide gene expression in striatal neurons through their connections with multiple intracellular effectors. This prominent involvement of mGluR in overall cellular activity is pivotal for the development of neuronal plasticity underlying long-term adaptive changes in cellular physiology related to a variety of neurologic disorders. Accumulating evidence demonstrates that the subtypes of mGluR have distinct effects on gene expression: group I subtypes facilitating, and group II/III subtypes inhibiting, gene expression. Thus, the mGluR can be considered as promising targets in the development of novel therapeutic drugs that can relieve neurologic disorders resulting from dysfunction of the striatum.